The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12968-019-0584-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different methods for the estimation of aortic pulse wave velocity from 4D flow cardiovascular magnetic resonance

Abstract: BackgroundArterial pulse wave velocity (PWV) is associated with increased mortality in aging and disease. Several studies have shown the accuracy of applanation tonometry carotid-femoral PWV (Cf-PWV) and the relevance of evaluating central aorta stiffness using 2D cardiovascular magnetic resonance (CMR) to estimate PWV, and aortic distensibility-derived PWV through the theoretical Bramwell-Hill model (BH-PWV). Our aim was to compare various methods of aortic PWV (aoPWV) estimation from 4D flow CMR, in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…This implies that MUSA may be a more reliable technique to calculate cPWV from OS PC‐MRI measured velocities. TTF method has been used extensively to quantify transit time of velocity waveforms with high temporal resolution obtained from ultrasound 19,26,50 . However, recent studies have reported that other transit‐time quantification algorithms could be more reliable when dealing with relatively lower temporal resolutions in PC‐MRI–based PWV measurements 29,37,51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that MUSA may be a more reliable technique to calculate cPWV from OS PC‐MRI measured velocities. TTF method has been used extensively to quantify transit time of velocity waveforms with high temporal resolution obtained from ultrasound 19,26,50 . However, recent studies have reported that other transit‐time quantification algorithms could be more reliable when dealing with relatively lower temporal resolutions in PC‐MRI–based PWV measurements 29,37,51 .…”
Section: Discussionmentioning
confidence: 99%
“…TTF method has been used extensively to quantify transit time of velocity waveforms with high temporal resolution obtained from ultrasound. 19,26,50 However, recent studies have reported that other transit-time quantification algorithms could be more reliable when dealing with relatively lower temporal resolutions in PC-MRI-based PWV measurements. 29,37,51 Also, it has been suggested that choosing the best algorithms might depend on the velocity waveform characteristics that are known to be different in various regions of vasculatures.…”
Section: F I G U R Ementioning
confidence: 99%
“…This ultimately enhances the signal to noise ratio in the resulting aortic images but might limit the usefulness in patients with counterindication to contrast agents. However, one might note that our segmentation technique was shown to be robust to low image quality, as it was able to reliably segment four‐dimensional flow MRI‐derived aortic angiograms, 36,37 which are known to have lower signal‐to‐noise ratio than conventional anatomical images. Our MRI data were acquired from three different sites using different field strengths (1.5 T and 3 T) and sequences (SPGR and SSFP).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was also shown that the estimation of aoPWV with 4D flow MRI can be obtained and reproduced using a full 3D coverage in the human aortic arch. The results were compared and significantly associated with standard PWV acquisition [ 127 ]. Four-dimensional PC MRI was also used to determine PWV and wall shear stress in the aortic arch at the same time [ 128 ].…”
Section: Arterial Wall Stiffness In Atherosclerosismentioning
confidence: 99%